ECONOMIC VALUATION OF ECOSYSTEM SERVICES: CARBON SEQUESTRATION AND STOCKS AT GREEN OPEN SPACE BASED ON COST OF ILLNESS (Cases in Tegalega, Sub-area of Bandung City) - Marisha, Sianne
Green Open Space is an open area as a place to grow plants that function as a balancer to urban ecosystems. Unfortunately, the condition of green open space has declined and impact on human health at a certain level. This study aims to measure the value of ecosystem services in terms of absorption and carbon stock based on the Cost of Illness (COI). To achieve this goal, it is necessary to measure CO2 absorption and carbon stock in green open space, calculate the COI, make a simulation of green space composition, and formulate a green open space provision strategy. The study was conducted at Tegalega, sub-area of Bandung City, which is the most populous area in Bandung. Data collection was carried out in two activities. The first one is the tree data collection and the second one is health problem data. Tree data collection was done by sampling as much as 15%. On the other hand, the health problem data was carried out through interviews with the COI method. The results showed that the potential of green open space in Tegalega to absorb carbon at this time was 126,313.96 kg CO2.year-.ha-1 and the current carbon stock at green open space was 47,319 kg. ha-1. The COI value that emerges from the availability of green open space is IDR 288,777,324,987 year-1. This value shows the high health costs that must be incurred due to carbon pollution in the air. From the COI value, the average value of one tree with services of absorbing and storing carbon is IDR 1,236,566,136. The value indicates the lack of green open space in Tegalega. To achieve the goal of reducing carbon pollution in the air, the green space model created is by selecting species with high CO2 absorption. The highest CO2 absorption is produced by planting Bauhinia purpurea in all fields, for polyculture with two trees is a combination of Cassia siamea and Polyalthia longifolia, three trees are Samanea saman, B. purpurea, and P. longifolia, four trees are S. saman, B purpurea, C. siamea and P. longifolia, a combination of five species of S. saman, B. purpurea, M. citrifolia, C. siamea, and P. longifolia, and a combination of seven species are S. saman, B. purpurea, M. citrifolia, C. siamea, P. longifolia, Syzigium zeylanicum, and Cerbera manghas. The results showed that species selection alone was not enough to provide green space, so other strategies with priority were needed, which are controlling, monitoring and evaluating existing green open space, providing education and training to the community, developing green open space on the remaining area, choosing multifunctional plants but according to their purpose, command and control for land developers, provide incentives and disincentives to communities that provide green open space, harmonize technology with green space planning, apply sanctions firmly, invite communities to plant in their environment, improve coordination between agencies in the provision of green open space, and develop private green open space more optimal.